Implementation of City Government Policy in Preserving Coastal Areas: a study in Pariaman City - Marhamah, Ithvi; Frinaldi, Aldri (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
Planning that is never in accordance with implementation is a deviation from regulations, violations of norms and non-compliance with laws and regulations. This research aims to analyze the implementation of space utilization policies based on the principles of coastal area sustainability in Pariaman City. The method used is a combination of qualitative and quantitative methods with a spatial approach using a Geographic Information System (GIS). The research results show that there is a harmonization analysis between Law Number 26 of 2007 Article 5 and Law Number 1 of 2014 Article 9 with the RTRW which is in principle appropriate. However, implementation in the field shows that there are built-up areas in zones that should be protected and buffer areas. The community's lack of knowledge about zoning, customary rights, and the city government's priorities for economic development through the tourism sector in coastal areas are the main factors in this deviation. This condition threatens the ecology and coastal resources, so it is necessary to strengthen policy implementation that involves effective community and government participation.